Characteristics and publication fate of unregistered and retrospectively registered clinical trials submitted to The BMJ over 4 years. Issue 2 (16th February 2018) - Loder, Elizabeth; Loder, Stephen; Cook, Sophie
Abstract : Objectives: We sought to evaluate the characteristics and publication fate of improperly registered clinical trials submitted to a medical journal ( The BMJ ) over a 4-year period to identify common types of registration issues and their relation to publication outcomes. Design: Research articles submitted to The BMJ and identified as unregistered or retrospectively registered by editors were included if they reported outcomes of a clinical trial. Relevant data regarding the trials were then extracted from each paper. Trials were categorised as prospectively registered, registered in an unapproved registry, unregistered or other, and explanations for registration deficiencies were grouped into six categories. We searched PubMed and Google to determine whether, where and when improperly registered studies were subsequently published and whether registration issues were disclosed. Results: 123 research papers reporting apparently unregistered or retrospectively registered clinical trials were identified. 110 studies (89.4%) were retrospectively registered, nine (7.3%) were unregistered, three (2.4%) had been registered in an unapproved registry and one study originally lacking registration details was later discovered to have been prospectively registered. 82 studies (66.6%) were funded entirely or in part by government sources, and only seven studies (5.7%) received funding from industry. Of those papers submitted to The BMJ through the end of 2015, 67 of the 70 papers rejected for registration problems (95.7%) were subsequently published in another journal. The registration problem was disclosed in only 2 (2.9%). Conclusions: Improper registration remains a problem, particularly for clinical trials that are government or foundation-funded. Nonetheless, improperly registered trials are almost always published, suggesting that medical journal editors may not actively enforce registration requirements.